Verstärkung im Editorial Board von GMS MBI gesucht - Reimann, Iris (GMS Medizin – Bibliothek – Information)
GMS MBI is published twice a year and is jointly edited by an editorial board. Anyone interested in joining the editorial board, in writing a review as part of the peer reviewing process or in being in charge of a single thematic issue is invited to express their interest.